THEORETICAL CALORIFIC VALUE ANALYSIS OF BRIQUETTE TEST RESULTS OF VARIATIONS OF BASIC MIXTURES OF ROBUSTA AND ARABIKA COFFEE - crisanto, bernardus; Novianto, Michael (Mechanical, Energy and Material (METAL), 2024)
Coffee grounds are waste produced from making coffee drinks, most of which are produced by coffee shops and usually this waste is just thrown away. Careless disposal of coffee grounds waste will certainly cause environmental damage, therefore one of the uses of coffee grounds waste in this research is as briquettes. The main ingredients used are robusta and arabica coffee grounds with mixed variations using the composition of 60% robusta, 40% arabica, 50% robusta 50% arabica and 40% arabica 60% robusta. The theoretical heating value calculation method is carried out through the results of heating water using a variety of briquettes, while the actual heating value is obtained from the results of the bomb calorimeter test. From the calculation and testing results, it was found that the theoretical heating value was identical to the test results, where the highest heating value was obtained in briquettes of the 40% Arabica 60% Robusta variation, amounting to 4919.835 cal/g for theoretical calculations and 4526.85 cal/g for bomb calorimeter test results. The theoretical calculation error rate for each comparative variation is 13.07% for the 60% Arabica 40% Robusta variation, 7.97% for the 50% Arabica 50% Robusta variation, and 8.68% for the 60% Arabica 40% Robusta variation